Factors that regulate expression patterns of insulin-like peptides and their association with physiological and metabolic traits in Drosophila. (August 2021) - Semaniuk, Uliana; Strilbytska, Olha; Malinovska, Karina; Storey, Kenneth B.; Vaiserman, Alexander; Lushchak, Volodymyr; Lushchak, Oleh
Abstract: Insulin-like peptides (ILPs) and components of the insulin signaling pathway are conserved across different animal phyla. Eight ILPs (called DILPs) and two receptors, dInR and Lgr3, have been described in Drosophila . DILPs regulate varied physiological traits including lifespan, reproduction, development, feeding behavior, stress resistance and metabolism. At the same time, different conditions such as nutrition, dietary supplements and environmental factors affect the expression of DILPs. This review focuses primarily on DILP2, DILP3, and DILP5 which are produced by insulin-producing cells in the brain of Drosophila . Although they are produced by the same cells and can potentially compensate for each other, DILP2, DILP3, and DILP5 expression may be differentially regulated at the mRNA level. Thus, we summarized available data on the conditions affecting the expression profiles of these DILPs in adult Drosophila . The accumulated data indicate that transcript levels of DILPs are determined by (a) nutritional conditions such as the protein-to-carbohydrate ratio, (b) carbohydrate type within the diet, (c) malnutrition or complete starvation; (d) environmental factors such as stress or temperature; (e) mutations of single peptides that induce changes in the expression of the other peptides; and (f) dietary supplements of drugs or natural substances. Furthermore, manipulation of specific genes in a cell- and tissue-specific manner affects mRNA levels for DILPs and, thereby, modulates various physiological traits and metabolism in Drosophila . Graphical abstract: Image 1 Highlights: Drosophila Insulin-like peptides regulate lifespan, reproduction, development, feeding behaviour and metabolism. Nutrition, dietary supplements and environmental factors affect the expression of DILPs. Manipulation of specific genes in a cell- and tissue-specific manner affects mRNA levels for DILPs.